Analisis Pengaruh Rotasi dan Mutasi Kerja Terhadap Kinerja Karyawan di KJKS BMT Anda Salatiga - Nur Aini; Tulus Tulus (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2015)
This study aims to determine whether job rotation and work mutation influence employee performance at BMT KJKS Anda Salatiga. Samples in this study are 31 respondents. This research uses primary data which are collected through interview and questionnaires. Multiple regression analysis is used as an analytical method in this research. The research shows that job rotation influences employee performance partially but work mutation does not. Job rotation and work mutation on does not influence employee performance simultaneously